Pengaruh Air Kelapa, Ekstrak Bawang Merah dan Ekstrak Rebung Bambu Terhadap Perkecambahan Benih Kopi Robusta (Coffea canephora) - Kirani, Aldila Putri Selsha; Pribadi, Didik Utomo; Triani, Nova (Universitas Muhammadiyah Prof. Dr. Hamka, 2024)
Background: Robusta (Coffea canephora) is one type of coffee widely cultivated in Indonesia and is one of the leading commodities. Coffee seeds include seeds that have a long dormancy period that inhibits the germination process. Breaking dormancy can be done by several methods, one of which is soaking in natural growth regulators. Soaking treatment with natural growth regulators can be combined with soaking time treatment to break dormancy. This study aimed to determine the combination of natural growth regulator treatment and the right soaking time for Robusta coffee seed germination. Methods: This research is a 3-repeat Complete Factorial Randomized Design Experiment with the first factor of natural growth regulators type, which consists of 4 levels, namely: Z0 = control; Z1 = coconut water; Z2 = onion extract and Z3 = bamboo shoots, and the second factor is the length of soaking which consists of 3 levels, namely P1 = 12 hours; P2 = 24 hours and P3 = 36 hours. Results: Natural growth regulators' treatment of shallot extract with 24 hours of soaking time gave the best results on all parameters. Conclusions: Using natural growth regulators from coconut water, shallots, and bamboo shoots with several soaking times affects all parameters observed, both in single and combined administration.